2020
DOI: 10.1186/s11689-020-09339-w
|View full text |Cite
|
Sign up to set email alerts
|

Long-term spatial tracking of cells affected by environmental insults

Abstract: Background Harsh environments surrounding fetuses and children can induce cellular damage in the developing brain, increasing the risk of intellectual disability and other neurodevelopmental disorders such as schizophrenia. However, the mechanisms by which early damage leads to disease manifestation in later life remain largely unknown. Previously, we demonstrated that the activation of heat shock (HS) signaling can be utilized as a unique reporter to label the cells that undergo specific molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…Lineage tracing is an effective method for monitoring cells of interest (and their progeny) over the long term, and has been used to explore CNS diseases. To examine how early damage can lead to disease in later life, Mohammad et al generated transgenic reporter mouse lines as a novel tool for long-term, systemic tracking of cells (and their progeny) that sustained damage in the prenatal environmental [ 70 ]. They demonstrated that the long-term effects of prenatal exposure to environmental insult are mediated by altered regulation of key molecules, which can cause epigenetic modifications that may be inherited by progeny.…”
Section: Lineage Tracing In Cns Diseasesmentioning
confidence: 99%
“…Lineage tracing is an effective method for monitoring cells of interest (and their progeny) over the long term, and has been used to explore CNS diseases. To examine how early damage can lead to disease in later life, Mohammad et al generated transgenic reporter mouse lines as a novel tool for long-term, systemic tracking of cells (and their progeny) that sustained damage in the prenatal environmental [ 70 ]. They demonstrated that the long-term effects of prenatal exposure to environmental insult are mediated by altered regulation of key molecules, which can cause epigenetic modifications that may be inherited by progeny.…”
Section: Lineage Tracing In Cns Diseasesmentioning
confidence: 99%
“…Genetic mutations and environmental insults may disrupt lineage development and impair neuronal diversification, which have been shown to predispose human beings to neurodevelopmental, neuropsychiatric, and neurodegenerative diseases [100][101][102]. Although previous studies have provided a wealth of knowledge on the molecular mechanisms of neural development, the genetic control of lineage specification in the developing brain remains underappreciated.…”
Section: Disruption Of Lineage Specification Causes Brain Disordersmentioning
confidence: 99%
“…Generation of the FASD mouse model was performed according to a previously published protocol [23,24], where pregnant CD-1 mice received an intraperitoneal injection (i.p.) of 25% ethanol (in PBS) solution at 4.0 g/kg bodyweight at embryonic day (E) 16 and 17.…”
Section: Acute Pae During Late Corticogenesis Leads To Anxiety Phenot...mentioning
confidence: 99%